Preliminary results of safety and efficacy of the interleukin 1 receptor antagonist anakinra in patients with severe lupus arthritis. Issue 4 (2nd September 2004) - Ostendorf, B; Iking-Konert, C; Kurz, K; Jung, G; Sander, O; Schneider, M
Abstract : Background: Joint involvement occurs in most patients with systemic lupus erythematosus (SLE), and severe lupus arthritis is often refractory to conventional treatments. Anakinra is used in the treatment of rheumatoid arthritis, but its therapeutic potential has not been proved in patients with SLE. Objective: To determine the safety/tolerability and efficacy of anakinra in patients with SLE with leading joint involvement. Methods: In patients with SLE with active polyarthritis and no other uncontrolled systemic/organ manifestations, 100 mg/day anakinra was self administered subcutaneously for 3 months. Disease activity was assessed by VAS, number of swollen/tender joints, ECLAM score, and serological and immunological measures. Results: Four patients with SLE were studied; anakinra was safe in all four patients and no drug related serious adverse events occurred. A subjective benefit was seen in all patients and a trend towards better activity measures after 4 weeks. After an initial response, one patient left the study because of an arthritic flare after 6 weeks. Conclusion: In this study anakinra was apparently safe and well tolerated and led to clinical and serological improvement. Anakinra might be an interesting alternative in individual patients with lupus arthritis not responding to conventional treatments.